TROPOSPHERIC DUCTS AND PLANETARY BOUNDARY LAYER STRUCTURE IN THE PETROLINA REGION - Sousa, Leandro Fontes de (2016)
The planetary boundary layer (PBL) structure is investigated focusing on days with low-tropospheric ducts occurrence in the Petrolina-PE region, in the period from 1 to 29 April 2014. Ducts identification and the estimative of the PBL top/height and its dynamic and thermodynamic characterization is based on 12 UTC upper-air soundings launched at the altitude station of Petrolina. Surface ducts are associated with high instability and wind speed intensification in the surface layer. Ducts at the PBL top (elevated ducts) are associated with a decrease in the moisture content of the air and a wind speed maximum, above the PBL, in the low-troposphere.